The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1007/s11356-014-4047-5
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of heavy metal contamination in Hediste diversicolor (O.F. Müller, 1776), Mugil cephalus (Linnaeus, 1758), and surface sediments of Bafa Lake (Eastern Aegean)

Abstract: In the present study, the bioaccumulation of six heavy metals (Cd, Cr, Cu, Hg, Pb, and Zn) in Hediste (Nereis) diversicolor (O.F. Müller, 1776) and also in the muscle and liver of Mugil cephalus (Linnaeus, 1758) collected from seven stations in the Bafa Lake was investigated. Sediment samples were also collected in each site to assess heavy metal levels and to provide additional information on pollution of the lake. The mean concentrations of heavy metals in sediment, H. diversicolor, and muscle and liver of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
5
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(9 citation statements)
references
References 38 publications
2
5
1
Order By: Relevance
“…Seasonal mean Cu concentrations measured in the sediment were found to be above the TEC values only at locations L2 and L3. The Cu concentrations measured within the scope of this study are compatible with those found in previous studies of the sediment in Lake Bafa 33,34 . Cu is a natural mineral that is abundant in nature, quite apart from its widespread use in industry and elsewhere 69 .…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…Seasonal mean Cu concentrations measured in the sediment were found to be above the TEC values only at locations L2 and L3. The Cu concentrations measured within the scope of this study are compatible with those found in previous studies of the sediment in Lake Bafa 33,34 . Cu is a natural mineral that is abundant in nature, quite apart from its widespread use in industry and elsewhere 69 .…”
Section: Discussionsupporting
confidence: 91%
“…Seasonal mean Cr concentrations exceeded TEC at all sampling points except C2, and at location L1, Cr was also measured at higher than PEC in autumn. High Cr concentrations were also found in previous studies of the sediment of Lake Bafa 33,34,35 . Its main sources are industrial wastewaters, mainly industrial leather wastewater and domestic wastewater 75 .…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations